Democratic control of intelligence services containing rogue elephants - Born, H. (Hans) 1964-; Caparini, Marina (Routledge, 2007)
This comprehensive volume discusses the various challenges of establishing and maintaining accountable and democratically controlled intelligence services, drawing both from states with well-established democratic systems and those emerging from authoritarian systems and in transition towards democracy